Multimodal flavour perception: the impact of sweetness, bitterness, alcohol content and carbonation level on flavour perception - Clark, Rebecca A. (2011)
Flavour perception of food and beverages is a complex multisensory experience involving the gustatory, olfactory, trigeminal, auditory and visual senses. Thus, investigations into multimodal flavour perception require a multidisciplinary design of experiments approach. This research has focussed on beer flavour perception and the fundamental interactions between the main flavour components - sweetness, bitterness (from hop acids), alcohol content and carbonation level. A model beer was developed using representative ingredients which could be manipulated to systematically vary the concentration of the main flavour components in beer and was used in the following experiments.